2007
DOI: 10.1111/j.1574-695x.2006.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic acid fromLactobacillus plantarumelicits both the production of Interleukin-23p19 and suppression of pathogen-mediated Interleukin-10 in THP-1 cells

Abstract: In this study, the stimulatory effects of different lactic acid bacteria strains, and their subcellular fractions, on the THP-1 cell line were evaluated. Lactobacillus plantarum was found in particular to induce high levels of IL-23p19 mRNA, but it moderately induced TNF-a production. IL-10 production was not entirely affected by L. plantarum stimulation. When subcellular fractions of L. plantarum were used to treat THP-1 cells, IL-23p19 mRNA expression was enhanced in a doseresponsive manner, specifically by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Furthermore, teichoic acids (TAs) from L. plantarum ATCC 14917 were found to be recognized by TLR2, activate the extracellular signal-regulated kinase pathway, and act synergistically with L. casei Shirota YIT9029 to induce IL-10 production in mouse peritoneal macrophages (55). However, other studies showed that expression of IL-10 was almost entirely unaffected in THP-1 cells after treatment with LTA isolated from L. plantarum KCTC10887BP (56) and that LTA from L. plantarum NCIMB8826 promotes IL-12 rather than IL-10 induction (57). Clearly, multiple Lactobacillus cell wall or secreted molecules could be directly involved in IL-10 mRNA induction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, teichoic acids (TAs) from L. plantarum ATCC 14917 were found to be recognized by TLR2, activate the extracellular signal-regulated kinase pathway, and act synergistically with L. casei Shirota YIT9029 to induce IL-10 production in mouse peritoneal macrophages (55). However, other studies showed that expression of IL-10 was almost entirely unaffected in THP-1 cells after treatment with LTA isolated from L. plantarum KCTC10887BP (56) and that LTA from L. plantarum NCIMB8826 promotes IL-12 rather than IL-10 induction (57). Clearly, multiple Lactobacillus cell wall or secreted molecules could be directly involved in IL-10 mRNA induction.…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell bacteria and subcellular bacterial fractions were prepared from S. flexneri (KCTC 2517), L. plantarum K8 (KCTC10887BP), and S. aureus (KCTC 1621) as previously described (Kim et al, 2007a). P. gingivalis LPS (PGLPS), muramyl dipeptide (MDP), Pam3CSK4, and monophosphoryl lipid A from S. minnesota (MPLA) were purchased from Invivogen (USA).…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…The purity of the purified LTA was determined by measuring the protein and endotoxin contents through the conventional silver staining after PAGE and through the Limulus amebocyte lysate assay (BioWhittaker), respectively. DNA or RNA contamination was assessed by measuring UV absorption at 260 and 280 nm (12). The modification of LTA from L. plantarum was performed as previously described with minor modifications (5, 13).…”
Section: Preparation and Modification Of Ltamentioning
confidence: 99%